The scars of COVID19: Preparing for the collateral damages - Dhar, Ruby; Jee, Babban; Pethusamy, Karthikeyan; Seethy, Ashikh; Kumar, Arun; Karmakar, Subhradip (Asian Journal of Medical Sciences, 2020)
COVID-19 is a pandemic of disproportionate magnitude. Its devastating effect seems to have a more significant impact on the emerging economies like India and the rest of SE Asia, which also has regions harbouring some of the world's highest population density living under poor socio-economic condition. What seems to have originated from one just one province in China, rapidly speard like wildfire across international territories, affecting millions and crippling the health care system. After about eight months into COVID-19, we realized that the fallout is not only humongous but also stretched across multiple avenues of the society and different aspects of our life. The scars of COVID-19 are much more than the virus itself. With a global shutdown in business and financial institutions, the economy is in free fall. Markets plummeted, stocks crashed and unemployment numbers skyrocketed. Apart from the economy, COVID-19 related shutdown has a tremendous impact on the healthcare system for those with preventable ailments, which were either compromised or delayed affecting millions who need hospitalization for non-COVID causes. COVID crisis also seems responsible for the emergence of a new culture system and mindset that was unprecedented before. With schools and other academic institutions closed, online teaching through electronic media and work from home became the new normal. In this editorial, we summarized the collateral damage on society, economy, and human health in the COVID crisis and few suggestions to chalk out a new plan and strategy to address the challenges for a future episode of similar nature. Though we could still remain vulnerable against similar contagious agents, an advanced planning strategy and preparedness will surely help us better in effective damage control and risk mitigation, not only to reduce mortality, but also from economic downfall.